2015
DOI: 10.1139/cjfr-2014-0428
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of Eucalyptus globulus harvest traits

Abstract: The cost of harvesting short-rotation plantation eucalypts can be in excess of AU$2500·ha−1. Despite this high cost, the extent to which harvesting productivity is affected by tree genetics is not well understood. We address this issue in a study of two 10-year-old genetic field trials of Eucalyptus globulus Labill. in Australia. Standing-tree traits analysed were survival, diameter at breast height, basal area, and stem straightness and forking. Harvest traits analysed were volume, time, and productivity. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The red line represents the overall average for the trial site , the blue line represents the historical climate average prior to the detectable signature of climate change in the southern hemisphere (Abram et al 2016(Abram et al ) (1911(Abram et al -1959, the green line corresponds to the climate average often used to represent the contemporary climate , and the grey line corresponds to the climate average during the growth period at the trial productive site. While harvesting productivity is positively related to tree size (Hamilton et al 2015), the extent and timing of the translation of ID from growth to survival are unlikely to have a significant economic impact on wood production in eucalypt plantations. This is because most small selfs would be expected to be dead by harvest age in the case of even short-rotation pulpwood regimes or to have been artificially thinned prior to harvest in the case of longer-rotation solid wood regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The red line represents the overall average for the trial site , the blue line represents the historical climate average prior to the detectable signature of climate change in the southern hemisphere (Abram et al 2016(Abram et al ) (1911(Abram et al -1959, the green line corresponds to the climate average often used to represent the contemporary climate , and the grey line corresponds to the climate average during the growth period at the trial productive site. While harvesting productivity is positively related to tree size (Hamilton et al 2015), the extent and timing of the translation of ID from growth to survival are unlikely to have a significant economic impact on wood production in eucalypt plantations. This is because most small selfs would be expected to be dead by harvest age in the case of even short-rotation pulpwood regimes or to have been artificially thinned prior to harvest in the case of longer-rotation solid wood regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Two adjoining unthinned and unpruned E. globulus genetic trials, herein referred to as Trial 1 and Trial 2, were studied. These trials were the subject of a previous study of growth and harvesting traits (Hamilton et al 2015a). Data from Trial 1 were used to estimate quantitative genetic parameters, and data from Trial 2 were used for QTL analyses.…”
Section: Genetic Materials and Trial Designsmentioning
confidence: 99%
“…The trial was designed according to a modified rowcolumn design at the plot level, where over-represented families were randomly assigned to plot positions of under-represented families. (see Freeman et al 2013 andHamilton et al 2015a, for more detailed descriptions of pedigrees and trail designs).…”
Section: Genetic Materials and Trial Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forking was the major stem form defect recorded in the current trial and accounted for 7% of the variation in harvester productivity. The proportion of forking in the current trial was much greater than that reported in recent trials in other Australian Eucalyptus globulus plantations [45,46]. The forking was likely to have mainly resulted from parrot damage recorded at the trial site as forking has been found to be the most common defect resulting from parrot damage [40].…”
Section: Discussionmentioning
confidence: 59%